PENGARUH OPINI AUDIT, PERGANTIAN MANAJEMEN DAN FEE AUDIT TERHADAP AUDITOR SWITCHING DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Perusahaan Real Estate & Property Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2011-2016) - Emrinald Emrinald; Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to analyze the influence of audit opinion, change of management and audit fee to auditor switching with financial distress as moderating variable. This research used purposive sampling method to get the sample for this research. The sample is a real estate and property companies which is listed on the Indonesia Stock Exchange (idx) in 2011-2016. For analysis the hypothesis of these variable is using logistic regression and moderated regression analysis (MRA). The test equipment used is a statistics program Statistical Package for Social Science (SPSS). The data used in the form of the companies financial reports contained on the website such as: Indonesian Capital Market Directory (ICMD), sharesOK and http://www.idx.co.id. The results of this research show that variable change of management and audit fee affect the auditor switching while variable audit opinion has no effect to auditor switching. Variable audit fee affect the auditor switching with financial distress as moderating variable while variable audit opinion and change of management has no effect to auditor switching with financial distress as moderating variable.Keywords : Auditor Switching, Audit Opinion, Change of Management, Audit Fee and Financial Distress